Chinese Herbal Medicine Improves the Long-Term Survival Rate of Patients With Chronic Kidney Disease in Taiwan: A Nationwide Retrospective Population-Based Cohort Study - Huang, Kuo-Chin; Su, Yuan-Chih; Sun, Mao-Feng; Huang, Sheng-Teng (Frontiers in Pharmacology, 2018)
Background and purpose: Chinese herbal medicine (CHM) is frequently applied in conjunction with western pharmacotherapy to relieve symptoms in patients with CKD. However, evidence-based research into the effectiveness of CHM use as applied to treat CKD is limited and warrants further investigation. The aim of this study is to assess whether adjunctive treatment with CHM affected survival rate of CKD patients undergoing conventional western medical management. Methods: A total of 14,718 CKD patients, including 6,958 CHM users and 7,760 non-CHM users, were recruited from the Longitudinal Health Insurance Database 2000, a sub-dataset of the National Health Insurance Research Database, to conduct this study. Demographic characteristics, including sex, age, job type, residential area, and comorbidity were considered as covariates to adjust the analysis. A network analysis of treatments, including with herbal formulas and single herbs, was performed to investigate the core patterns of CHM use for the treatment of CKD patients. The Kaplan-Meier method was used to determine the survival rate between CHM and non-CHM groups. Results: After matching for sex and age, there were 550 subjects in both the CHM and non-CHM cohorts. Other than presence of diabetes (adjusted OR = 0.57, p < 0.001) and urinary tract infection (adjusted OR = 0.69, p < 0.05), sex, age, job type, area of residence, and other comorbidities indicated no special preference for CHM use among subjects. Salvia miltiorrhiza Bunge (SM) and Ji-Sheng-Shen-Qi-Wan (JSSQW) were the most frequent single herb and formula, respectively, prescribed for patients with CKD. The most frequent CHM combination between herbs and formulas was JSSQW, associated with Rheum officinale Baill. (RO), SM and Astragalus membranaceus (Fisch.) Bunge (AM). The long-term survival rate demonstrated significant benefits for CHM users within a 12-year follow-up period (P < 0.004). Conclusions: This nationwide retrospective cohort study provides valuable insight into the characteristics and prescription patterns of CHM usage in CKD patients. JSSQW associated with RO, SM and AM is the most common CHM prescription. CHM improves long-term survival in patients with CKD, suggesting that CHM is an effective adjuvant therapy for CKD.